Sistematización de la experiencia de elaboración de un manual de funciones y diseño del proceso de selección en la Empresa Creamoda en la ciudad de Quito durante el periodo enero 2017 – julio 2017 - Minango Chalco, Evelin Angelica (2018)
The systematization project arises from a need of the company CREAMODA to have tools that will regulate the functioning of the processes related to the management of human talent since the company does not have a department or person in charge of controlling this area. This shortage was causing a malfunction of the company due to the fact that it was not known how to adequately carry out the process of selecting new workers and, in addition, there was no manual of functions that would let workers know the tasks that they must execute. For this reason, it is decided to design a function manual for the positions defined in the organization chart, in addition to establishing the flow chart of the personnel selection process. In order to achieve the desired results, techniques and tools of the qualitative methodology such as observation and information gathering were applied. The business tools obtained are adapted to standards established by the ANSI and ISO for this type of documentation and are cataloged by the company as a contribution of vital importance for its operation and productivity because they provide documentary evidence of what to do and how to do it.